Developing novel hybrid reefs to provide both wave energy reduction and opportunities for ecological restoration - Benjamin K. Norris; Borja G. Reguero; Camila Gaido-Lasserre; David Gutierrez-Barcelo; Joseph Bartolai; Michael A. Yukish; Landolf Rhode-Barbarigos; Brian K. Haus; Taylor Squires; Gabriel Barajas Ojeda; Maria Maza; Javier L. Lara; et al. (Coastal Engineering, 2026)

Fissure locations and fire-fountain dynamics during the December 2023–September 2024 Svartsengi Volcanic System eruptions, Iceland, from aerial imagery and recreational webcam footage - Rebekah S. Rhodes; David M. Pyle; Tamsin A. Mather; Gro B. M. Pedersen; Michelle M. Parks (Bulletin of Volcanology, 2026)
Recent fissure-fed eruptions from the Svartsengi Volcanic System have significantly impacted Iceland’s Reykjanes Peninsula. With eruptions likely to continue intermittently for decades to centuries, exploring the controls on the locations of fissure-fed eruptions is important for hazard assessment and risk mitigation. This study maps eruptive fissures from six eruptions from December 2023 to September 2024 using satellite and aerial imagery and observes fire-fountain height evolution for four eruptions using webcam footage. We find that fissure locations are heavily influenced by topography, including features parallel to fissure strike and features formed during previous eruptions. The maximum fire-fountain heights ranged from 56 m during the January 2024 eruption to 133 m during the August 2024 eruption. Variations in fire-fountain heights in a single eruption between different fissure segments, and through time, appear to primarily be controlled by surface vent size and dike pressurisation, both of which increase mass eruption rate and lead to higher fountains. Understanding the controls on fissure location highlights areas most vulnerable to future fissure opening, which can help inform ongoing hazard assessment and risk mitigation. Digital video capture of future eruptions from multiple angles would augment monitoring and help refine models of fire-fountain evolution.

Advancing provitamin A biofortification in sorghum: from allele mining and marker development to prebreeding and breeding - Clara Cruet-Burgos; Linly Banda; Jacques M. Faye; Cyril Diatta; David Zapata; Geoffrey P. Morris; Davina H. Rhodes (Theoretical and Applied Genetics, 2026)
Key message Allele mining for provitamin A biofortification in sorghum is advanced with new pre-bred germplasm and markers that are trait-predictive in diverse germplasm and breeding programs. Abstract Provitamin A biofortification of the staple cereal crop sorghum ( Sorghum bicolor [L.] Moench) could reduce vitamin A deficiency in low-income countries of sub-Saharan Africa. To advance mining of alleles that confer high provitamin A from genebank accessions, we developed prebreeding germplasm and trait-predictive markers, and established the utility of these markers in a range of prebreeding and breeding materials. We first tested the hypothesis that carotenoid concentrations in sorghum grain can be increased through breeding using six biparental families developed from high-carotenoid genebank accessions. The families exhibited abundant transgressive segregation for carotenoid concentrations, with positive asymmetry in many cases (4 of 6 families) suggesting the release of epistatic variation. Next, we developed eleven markers from SNPs associated with carotenoid variation, and validated their predictiveness in the six biparental families and diverse global germplasm. Two markers (snpSB00267 and snpSB00276), previously identified as zeaxanthin QTLs, were predictive of provitamin A content (β-carotene) in the biparental family evaluated and the diverse germplasm, and require further validation. Five markers that were predictive of zeaxanthin content—most notably snpSB00265, located within the zeaxanthin epoxidase ( ZEP ) gene; snpSB00277 and snpSB00264, near ZEP ; and snpSB00279 and snpSB00280, in the β-carotene 3-hydroxylase gene—are recommended for indirect selection for provitamin A carotenoids. In a Senegalese breeding program, most markers (9 of 11) were segregating and contrasted for the elite germplasm (low carotenoid alleles) and yellow-endosperm donor lines (high carotenoid). Together, findings show that sorghum grain carotenoids can be increased through breeding, and demonstrate the potential of marker-assisted selection for provitamin A biofortification.

Development and validation of matrix-validated LC–MS/MS method for simultaneous quantification of 21 neonicotinoids and their metabolites in human urine - Wenjing Xi; Sarah Onysio; Mary C. Rhodes; Alexis J. Faudel; John C. Flunker; Mark K. Santillan; Donna A. Santillan; David M. Cwiertny; Darrin A. Thompson (Environmental Science and Pollution Research, 2026)
Neonicotinoids (NEOs) are the most widely used class of insecticides worldwide. Consequently, human exposure occurs through multiple pathways, including dietary intake and environmental contact. Previous analytical methods have primarily focused on parent compounds, often excluding key metabolites due to matrix effects and poor quantification in complex biological samples. This gap severely limits the ability to accurately assess total NEO exposure and internal dose, highlighting the urgent need for more comprehensive and reliable biomonitoring approaches. This study developed a comprehensive LC–MS/MS method to quantify 21 NEOs and metabolites in human urine, uniquely including key transformation products such as clothianidin-n-desmethyl, clothianidin-urea, imidacloprid-urea, imidacloprid-olefin, 5-hydroxy-imidacloprid, thiamethoxam-urea, and thiamethoxam-n-desmethyl, thereby enabling a more thorough assessment of human exposure to NEOs. The method was validated using both synthetic and pooled human urine, providing a critical assessment of matrix-dependent variations in detection limits, accuracy, and precision. Method performance demonstrated high sensitivity, specificity, accuracy, and precision, with limits of quantification (LOQ) from 0.017 to 0.46 ng/mL and limits of detection (LOD) from 0.0050 to 0.14 ng/mL. The method was applied to urine samples from 246 pregnant women and 47 farmers in eastern Iowa to assess exposure levels. Results indicated widespread NEO exposure with detection frequencies of 99% of pregnant women and 100% in farmers, with 18 different NEOs and metabolites detected across both populations. Metabolite monitoring revealed that imidacloprid metabolites (IMI-O, 5-OH-IMI) were stronger predictors of total neonicotinoid burden than parent compounds alone ( r s = 0.735 vs < 0.6 for parents), with some metabolites showing higher concentrations in pregnant women than farmers despite farmers having higher overall exposure. These findings demonstrate that parent-only biomonitoring substantially underestimates internal neonicotinoid exposure and fails to capture critical exposure pathways, particularly for vulnerable populations where metabolite patterns may differ significantly from occupational exposure profiles.

Does fishery management for groupers (Teleostei: Epinephelidae) protect them effectively? Context from the IUCN's Red list of threatened species - Sean T. Fennessy; Christi Linardich; Kevin Rhodes; Joao P. Barreiros; David Pollard; Eloy Sosa-Cordero; Felicia Coleman; Alfonso Aguilar-Perera; Christopher R. Malinowski; Thierry Brulé; Pedro Afonso; Kayan Ma; et al. (Ocean & Coastal Management, 2026)

Swift SNPs: Evaluating Rapid DNA Extraction Methods for Scalable Genotyping in Aquaculture - Emily Rhodes; Dean Jerry; David B. Jones; Julie Goldsbury; Nga Vu (Marine Biotechnology, 2026)
Efficient DNA extraction is critical for high-throughput genotyping in aquaculture breeding programs, where cost, speed, and data quality must be balanced. This study compared five rapid extraction methods—HotSHOT, Chelex, Tween, wax-coated dipstick, and bare dipstick—against a conventional cetyltrimethylammonium bromide (CTAB) protocol for use in Lates calcarifer (barramundi) genotyping. DNA yield, purity, and integrity were measured by spectrophotometry, fluorometry, and Agilent TapeStation. Performance was tested in microsatellite genotyping, tyrosinase-related protein 1b (TYRP1b) gene sequencing, and single nucleotide polymorphism (SNP) genotyping on the Tecan Allegro Targeted Resequencing V2 platform. CTAB produced the highest-quality DNA (30.3 ± 17.4 ng/µL; A260/A280 = 1.91 ± 0.26; DIN = 8.78) with reliable results in all assays. Despite lower quality (1.07 ± 0.30 ng/µL; A260/A280 = 1.44 ± 0.18; DIN ≈ 1.6), HotSHOT performed similarly: SNP concordance with CTAB averaged 82.3%, microsatellite amplification reached 93.1% (vs. 99.3% for CTAB), and all HotSHOT samples yielded high-quality TYRP1b sequences. Chelex, Tween, and dipstick methods had lower success, likely due to inadequate yield and purity. HotSHOT was the most effective rapid alternative to CTAB, with significantly higher SNP concordance (82.3% vs. others; p < 0.005). These results show that method choice strongly influences target-capture genotyping success and support HotSHOT as a cost-effective, scalable option for aquaculture genomics.

Prediction of Clinically Significant Improvements During the Interdisciplinary Intensive Outpatient Program for Traumatic Brain Injury Using Machine Learning - Rujirutana Srikanchana; David Samuel; Jacob Powell; Treven Pickett; Thomas DeGraba; Chandler Sours Rhodes (Annals of Biomedical Engineering, 2025)

A Randomised Controlled Trial of SFX-01 After Subarachnoid Haemorrhage — The SAS Study - Ardalan Zolnourian; Patrick Garland; Patrick Holton; Mukul Arora; Jonathan Rhodes; Christopher Uff; Tony Birch; David Howat; Stephen Franklin; Ian Galea; Diederik Bulters (Translational Stroke Research, 2025)
SFX-01 is a novel drug for clinical delivery of sulforaphane (SFN). SFN is a potent nuclear factor erythroid 2-related factor 2 activator that reduces inflammation and oxidation, improving outcomes after subarachnoid haemorrhage (SAH) in animal models. This was a multi-centre, double-blind, placebo-controlled, parallel-group randomised clinical trial to evaluate the safety, pharmacokinetics and efficacy of 28 days of SFX-01 300 mg BD in patients aged 18–80 with spontaneous SAH and high blood load on CT. Primary outcomes were (1) safety, (2) plasma and CSF SFN and metabolite levels and (3) vasospasm on transcranial doppler ultrasound. Secondary outcomes included CSF haptoglobin and malondialdehyde and clinical outcome on the modified Rankin Scale (mRS) and SAH outcome tool (SAHOT). A total of 105 patients were randomised (54 SFX-01, 51 placebo). There were no differences in adverse events other than nausea (9 SFX-01 (16.7%), 1 placebo (2.0%)). SFN, SFN-glutathione and SFN-N-acetyl-cysteine AUC last were 16.2, 277 and 415 h × ng/ml. Plasma SFN was higher in GSTT1 null individuals ( t = 2.40, p = 0.023). CSF levels were low with many samples below the lower limit of quantification and predicted by the CSF/serum albumin ratio ( R 2 = 0.182, p = 0.039). There was no difference in CSF haptoglobin (1.981 95%CI 0.992–3.786, p = 0.052) or malondialdehyde (1.12 95%CI 0.7477–1.687, p = 0.572) or middle cerebral artery flow velocity (1.04 95%CI 0.903–1.211, p = 0.545) or functional outcome (mRS 1.647 95%CI 0.721–3.821, p = 0.237, SAHOT 1.082 95%CI 0.464–2.525, p = 0.855). SFX-01 is safe and effective for the delivery of SFN in acutely unwell patients. SFN penetrated CSF less than expected and did not reduce large vessel vasospasm or improve outcome. Trial registration: NCT02614742 clinicaltrials.gov.

Home range and resource selection of Virginia opossums in the rural southeastern United States - Jacob E. Hill; David A. Bernasconi; Richard B. Chipman; Amy T. Gilbert; James C. Beasley; Olin E. Rhodes; Guha Dharmarajan (Mammal Research, 2024)

Bioaccumulation of contaminants in Scarabaeidae and Silphidae beetles at sites polluted by coal combustion residuals and radiocesium - Ansley E. Silva; Robert J. Speakman; Brittany F. Barnes; David R. Coyle; James C. Leaphart; Erin F. Abernethy; Kelsey L. Turner; Olin E. Rhodes; James C. Beasley; Kamal J.K. Gandhi (Science of The Total Environment, 2023)

Assessing efficiency of fine-mapping obesity-associated variants through leveraging ancestry architecture and functional annotation using PAGE and UKBB cohorts - Mohammad Yaser Anwar; Mariaelisa Graff; Heather M. Highland; Roelof Smit; Zhe Wang; Victoria L. Buchanan; Kristin L. Young; Eimear E. Kenny; Lindsay Fernandez-Rhodes; Simin Liu; Themistocles Assimes; David O. Garcia; et al. (Human Genetics, 2023)

Inflammatory profiles, gut microbiome, and kidney function are impacted after high-fidelity firefighter training - Madelyn C. Houser; Daniel J. Smith; David Rhodes; Judith L. Glick-Smith; Phillip Chovan; Erin Ferranti; Sandra B. Dunbar; Malú G. Tansey; Vicki Hertzberg; Valerie V. Mac (International Journal of Hygiene and Environmental Health, 2023)

Temporal and geographic extent of the late Holocene dry period in the central Great Basin, USA - Scott Mensing; Wei Wang; David Rhode; Douglas J. Kennett; Adam Csank; David Hurst Thomas; Cedar Briem; Thomas K. Harper; Brendan J. Culleton; Richard J. George; John Southon (Quaternary Science Reviews, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Examining the Role of Marine Mammals and Seabirds in Southeast Alaska’s Marine Ecosystem Dynamics - Melissa Rhodes-Reese; David Clay; Curry Cunningham; Janet Moriles-Miller; Cheryl Reese; Joe Roman; Joseph D. Warren; Heidi C. Pearson (Frontiers in Marine Science, 2021)
Primary producers are the foundation of marine food webs and require reliable nutrient sources to maintain their important role with ecosystems. While marine mammals and seabirds can play critical roles in marine nutrient cycling, their contributions are often overlooked. Southeast Alaska’s marine environment supports abundant marine mammal and seabird populations in addition to valuable fisheries. Nonetheless, there is still relatively little known about nutrient sources and fluxes in this region which is a critical component of fisheries management. The goal of our study was to advance knowledge of the role of mammals and seabirds in marine nutrient cycling and to understand how changing marine mammal and seabird populations may alter ecosystem dynamics. We utilized qualitative network models (QNMs) to examine how a simulated Southeast Alaska ecosystem would respond to an increase in marine mammals, seabirds, and nutrients. Researchers are increasingly utilizing QNMs as a first step in the development of ecosystem-based fisheries management plans as their adaptable nature is well suited to address rapidly changing climatic conditions. Our results indicate that marine mammals and seabirds make important contributions to marine nutrient concentrations in the region and that these valuable ecosystem services should not be overlooked.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Impact of Pleistocene–Holocene climate shifts on vegetation and fire dynamics and its implications for Prearchaic humans in the central Great Basin, USA - Sandra Olivia Brugger; David Rhode (Journal of Quaternary Science, 2020)
The effects of climate change during the Terminal Pleistocene–Early Holocene transition on ecosystems and early Prearchaic hunter‐gatherers in the central Great Basin of North America are not well understood. We present a palynological reconstruction of regional vegetation and fire history in Grass Valley, central Nevada, from ~14 to ~7.5k cal a BP showing that Pinus ‐dominated woodlands were replaced by dry‐adapted steppe and desert vegetation accompanied by an increase in regional fire activity at the beginning of the Holocene, in response to summer warming and a drying climate. Following a severe drought period peaking ~10.2–9.3k cal a BP, Pinus woodlands partially recovered contemporaneously with the 8.2k cal a BP climate anomaly. Local wetlands provided important resource patches for human foraging societies, and periodic declines of wetlands in response to changing local hydrological conditions may have necessitated adjustments in subsistence and settlement practices and technology.

Decreased grey matter volume in mTBI patients with post-traumatic headache compared to headache-free mTBI patients and healthy controls: a longitudinal MRI study - Shana A. B. Burrowes; Chandler Sours Rhodes; Timothy J. Meeker; Joel D. Greenspan; Rao P. Gullapalli; David A. Seminowicz (Brain Imaging and Behavior, 2020)

A Qualitative Systematic Review of Cigarette Smoking Cessation Interventions for Persons Living with HIV - Lilli Mann-Jackson; David Choi; Erin L. Sutfin; Eunyoung Y. Song; Kristie L. Foley; Aimee M. Wilkin; Caryn G. Morse; Nicole F. Rojas; Timothy S. Oh; Scott D. Rhodes (Journal of Cancer Education, 2019)

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

Bioactive glycosides from the African medicinal plant Boerhavia erecta L. - Ari S. Nugraha; Adama Hilou; Nicholas Vandegraaff; David I. Rhodes; Rachada Haritakun; Paul A. Keller (Natural Product Research, 2015)

The rulB gene of plasmid pWW 0 is a hotspot for the site‐specific insertion of integron‐like elements found in the chromosomes of environmental P seudomonas fluorescens group bacteria - Glenn Rhodes; Hester Bosma; David Studholme; Dawn L. Arnold; Robert W. Jackson; Roger W. Pickup (Environmental Microbiology, 2014)
Summary The rulAB operon of P seudomonas spp. confers fitness traits on the host and has been suggested to be a hotspot for insertion of mobile elements that carry avirulence genes. Here, for the first time, we show that rulB on plasmid pWW 0 is a hotspot for the active site‐specific integration of related integron‐like elements ( ILE s) found in six environmental pseudomonads (strains FH 1– FH 6). Integration into rulB on pWW 0 occurred at position 6488 generating a 3 bp direct repeat. ILE s from FH 1 and FH 5 were 9403 bp in length and contained eight open reading frames ( ORF s), while the ILE from FH 4 was 16 233 bp in length and contained 16 ORF s. In all three ILE s, the first 5.1 kb (containing ORF s 1–4) were structurally conserved and contained three predicted site‐specific recombinases/integrases and a tetR homologue. Downstream of these resided ORF s of the ‘variable side’ with structural and sequence similarity to those encoding survival traits on the fitness enhancing plasmid pGRT 1 ( ILE FH 1 and ILE FH 5 ) and the NR‐II virulence region of genomic island PAGI ‐5 ( ILE FH 4 ). Collectively, these ILEs share features with the previously described type III protein secretion system effector ILEs and are considered important to host survival and transfer of fitness enhancing and (a)virulence genes between bacteria.

Late Quaternary Qaidam lake histories and implications for an MIS 3 “Greatest Lakes” period in northwest China - David B. Madsen; ZhongPing Lai; YongJuan Sun; David Rhode; XiangJun Liu; P. Jeffrey Brantingham (Journal of Paleolimnology, 2014)

In-silico modeling of atrial repolarization in normal and atrial fibrillation remodeled state - Martin W. Krueger; Andreas Dorn; David U. J. Keller; Fredrik Holmqvist; Jonas Carlson; Pyotr G. Platonov; Kawal S. Rhode; Reza Razavi; Gunnar Seemann; Olaf Dössel (Medical & Biological Engineering & Computing, 2013)

Fishing groupers towards extinction: a global assessment of threats and extinction risks in a billion dollar fishery - Yvonne Sadovy de Mitcheson; Matthew T Craig; Athila A Bertoncini; Kent E Carpenter; William W L Cheung; John H Choat; Andrew S Cornish; Sean T Fennessy; Beatrice P Ferreira; Philip C Heemstra; Min Liu; Robert F Myers; et al. (Fish and Fisheries, 2013)
Groupers are a valuable fishery resource of reef ecosystems and are among those species most vulnerable to fishing pressure because of life history characteristics including longevity, late sexual maturation and aggregation spawning. Despite their economic importance, few grouper fisheries are regularly monitored or managed at the species level, and many are reported to be undergoing declines. To identify major threats to groupers, the International Union for Conservation of Nature (IUCN) Red List criteria were applied to all 163 species. Red List assessments show that 20 species (12%) risk extinction if current trends continue, and an additional 22 species (13%) are considered to be Near Threatened. The Caribbean Sea, coastal Brazil and Southeast Asia contain a disproportionate number of Threatened species, while numerous poorly documented and Near Threatened species occur in many regions. In all, 30% of all species are considered to be Data Deficient. Given that the major threat is overfishing, accompanied by a general absence and/or poor application of fishery management, the prognosis for restoration and successful conservation of Threatened species is poor. We believe that few refuges remain for recovery and that key biological processes (e.g. spawning aggregations) continue to be compromised by uncontrolled fishing. Mariculture, through hatchery‐rearing, increases production of a few species and contributes to satisfying high market demand, but many such operations depend heavily on wild‐caught juveniles with resultant growth and recruitment overfishing. Better management of fishing and other conservation efforts are urgently needed, and we provide examples of possible actions and constraints.

Management of Concentrated Waste Streams from High-Pressure Membrane Water Treatment Systems - Stuart J. Khan; David Murchland; Michelle Rhodes; T. David Waite (Critical Reviews in Environmental Science and Technology, 2009)

Fine-mapping the genetic basis of CRP regulation in African Americans: a Bayesian approach - Benjamin Rhodes; David L. Morris; Lakshman Subrahmanyan; Cristin Aubin; Carlos F. Mendes de Leon; Jeremiah F. Kelly; Dennis A. Evans; John C. Whittaker; Jorge R. Oksenberg; Philip L. De Jager; Tim J. Vyse (Human Genetics, 2008)

Biomass with capture: negative emissions within social and environmental constraints: an editorial comment - James S. Rhodes; David W. Keith (Climatic Change, 2008)

Plastic responses to temporal variation in moisture availability: consequences for water use efficiency and plant performance - Joshua J. Picotte; David M. Rosenthal; Jennifer M. Rhode; Mitchell B. Cruzan (Oecologia, 2007)

ET743: Chemical analysis of the sea squirt Ecteinascidia turbinata ecosystem - Thomas Manning; Emily Rhodes; Richard Loftis; Dennis Phillips; Don Demaria; David Newman; Jack Rudloe (Natural Product Research, 2006)

DNA-based therapeutics and DNA delivery systems: A comprehensive review - Siddhesh D. Patil; David G. Rhodes; Diane J. Burgess (The AAPS Journal, 2005)

Anionic liposomal delivery system for DNA transfection - Siddhesh D. Patil; David G. Rhodes; Diane J. Burgess (The AAPS Journal, 2004)

Methylphenidate restores visual memory, but not working memory function in attention deficit-hyperkinetic disorder - Sinead M. Rhodes; David R. Coghill; Keith Matthews (Psychopharmacology, 2004)

Acidity of exogenous metal ion in the activation of calcineurin - David J. Rhode; Bruce L. Martin (BioMetals, 2004)

Postfire Management on Forested Public Lands of the Western United States - ROBERT L. BESCHTA; JONATHAN J. RHODES; J. BOONE KAUFFMAN; ROBERT E. GRESSWELL; G. WAYNE MINSHALL; JAMES R. KARR; DAVID A. PERRY; F. RICHARD HAUER; CHRISTOPHER A. FRISSELL (Conservation Biology, 2004)
Forest ecosystems in the western United States evolved over many millennia in response to disturbances such as wildfires. Land use and management practices have altered these ecosystems, however, including fire regimes in some areas. Forest ecosystems are especially vulnerable to postfire management practices because such practices may influence forest dynamics and aquatic systems for decades to centuries. Thus, there is an increasing need to evaluate the effect of postfire treatments from the perspective of ecosystem recovery. We examined, via the published literature and our collective experience, the ecological effects of some common postfire treatments. Based on this examination, promising postfire restoration measures include retention of large trees, rehabilitation of firelines and roads, and, in some cases, planting of native species. The following practices are generally inconsistent with efforts to restore ecosystem functions after fire: seeding exotic species, livestock grazing, placement of physical structures in and near stream channels, ground‐based postfire logging, removal of large trees, and road construction. Practices that adversely affect soil integrity, persistence or recovery of native species, riparian functions, or water quality generally impede ecological recovery after fire. Although research provides a basis for evaluating the efficacy of postfire treatments, there is a continuing need to increase our understanding of the effects of such treatments within the context of societal and ecological goals for forested public lands of the western United States.

Cloning and expression of pkaC and pkaR, the genes encoding the cAMP-dependent protein kinase of Aspergillus fumigatus - Brian G. Oliver; John C. Panepinto; Jarrod R. Fortwendel; Darcey L. Smith; David S. Askew; Judith C. Rhodes (Mycopathologia, 2002)

Bury, Burn or Both: A Two-for-One Deal on Biomass Carbon and Energy - David W. Keith; James S. Rhodes (Climatic Change, 2002)

Molecular Cloning of cgrA, the Gene Encoding the Aspergillus nidulans Ortholog of Saccharomyces cerevisiae CGR1 - Jianlan Sun; Douglas Boettner; Nichole Huebner; Fan Xu; Judith C. Rhodes; David S. Askew (Current Microbiology, 2001)

SEM Imaging Predicts Quality of Niosomes from Maltodextrin-Based Proniosomes - Almira I. Blazek–Welsh; David G. Rhodes (Pharmaceutical Research, 2001)

Cgr1p, a Novel Nucleolar Protein Encoded by Saccharomyces cerevisiae Orf YGL0292w - Jianlan Sun; Molly McFarland; Douglas Boettner; John Panepinto; Judith C. Rhodes; David S. Askew (Current Microbiology, 2001)

Petrology and geochronology of basalt breccia from the 1996 earthquake swarm of Loihi seamount, Hawaii: magmatic history of its 1996 eruption - Michael O. Garcia; Kenna H. Rubin; Marc D. Norman; J. Michael Rhodes; David W. Graham; David W. Muenow; Khalil Spencer (Bulletin of Volcanology, 1998)

Iron supplementation moderates but does not cure the Belgrade anemia - Michael Garrick; Donna Scott; Susannah Walpole; Eric Finkelstein; Joy Whitbred; Sandeep Chopra; Lalitha Trivikram; David Mayes; Daphne Rhodes; Kimberly Cabbagestalk; Rahmi Oklu; Adnan Sadiq; et al. (BioMetals, 1997)